Islam in the West : perceptions and reactions - Ata, Abe W; Ali, Jan A. (New Delhi, India : Oxford University Press, 2018)
This book focuses on the way Muslims and mainstream societies in the West, especially in America, Australia, and Europe, perceive each other. It focuses on the meaning of being a Muslim in a multicultural, multi-religious, and technologically developed world.
Includes bibliographical references and index.
Karim International
Keywords: Muslims -- Australia -- Attitudes; English language; Muslims -- Western countries -- Attitudes; Australians -- Attitudes; Muslims -- Australia -- Ethnic identity; Muslims -- Western countries -- Ethnic identity; Australians -- Attitudes; Muslims -- Attitudes; Muslims -- Ethnic identity; Australia; Western countries; Australian